Design and Modelling of Water Chilling Production System by the Combined Effects of Evaporation and Night Sky Radiation - Al-Zubaydi, Ahmed Y. Taha; Dartnall, W. John (Journal of Renewable Energy, 2014)
The design and mathematical modelling of thermal radiator panel to be used primarily to measure night sky radiation wet coated surface is presented in this paper. The panel consists of an upper dry surface coated aluminium sheet laminated to an ethylene vinyl acetate foam backing block as an insulation. Water is sprayed onto the surface of the panel so that an evaporative cooling effect is gained in addition to the radiation effect; the surface of a panel then is wetted in order to study and measure the night sky radiation from the panel wet surface. In this case, the measuring water is circulated over the upper face of this panel during night time. Initial TRNSYS simulations for the performance of the system are presented and it is planned to use the panel as calibrated instruments for discriminating between the cooling effects of night sky radiation and evaporation.